WEB DESIGN SOLUTIONS FOR DETECTING DISEASE AND HEALING RECOMMENDATIONS USING MACROMEDIA DREAMWEAVER MX. - Annisa Fadlila Ulfa; Rev. Linda Widianti, Skom., MMSI (Jurnal Sistem Informasi, 2008)
Along with a fairly rapid development of technology today, the use of technology in the medical world had already begun to develop. Utilization of technology to cure already done a lot. But it is still not effective  enough, because the identification of early disease is crucial for early preventive measures and first aid.  Harnessing technology to identify early symptoms of disease based on the felt, with computer technology using a program that is Macromedia Dreamweaver MX.